Non-viral TRAC-knocked-in CD19KICAR-T and gp350KICAR-T cells tested against Burkitt lymphomas with type 1 or 2 EBV infection: In vivo cellular dynamics and potency - Braun, Tobias; Pruene, Alina; Darguzyte, Milita; vom Stein, Alexander F.; Nguyen, Phuong-Hien; Wagner, Dimitrios L.; Kath, Jonas; Roig-Merino, Alicia; Heuser, Michael; Riehm, Lucas L.; Schneider, Andreas; Awerkiew, Sabine; et al. (Frontiers in Immunology, 2023)
The ubiquitous Epstein-Barr virus (EBV) is an oncogenic herpes virus associated with several human malignancies. EBV is an immune evasive pathogen that promotes CD8+ T cell exhaustion and dysregulates CD4+ T cell functions. Burkitt lymphoma (BL) is frequently associated with EBV infections. Since BL relapses after conventional therapies are hard to treat, we evaluated prospective off-the-shelf edited CAR-T cell therapies targeting CD19 or the EBV gp350 cell surface antigen. We used CRISPR/Cas9 gene editing methods to knock-in (KI) the CD19CAR.CD28z or gp350CAR.CD28z into the T cell receptor (TCR) alpha chain (TRAC) locus. Applying up-scaled methods with the ExPERT ATx ® MaxCyte system, the KI efficacy was ~20% of the total ~2x108 TCR-knocked-out (KO) generated cells. KOTCRKICAR-T cells were co-cultured in vitro with the gp350+CD19+ BL cell lines Daudi (infected with a type 1 EBV) or with Jiyoye (harboring a lytic type 2 EBV). Both types of CAR-T cells showed cytotoxic effects against the BL lines in vitro. CD8+ KICAR-T cells showed higher persistency than CD4+ KICAR-T cells after in vitro co-cultures with BL, and upregulation of the activation / exhaustion markers PD-1, LAG-3 and TIM-3. Two preclinical in vivo xenograft models were set up with Nod.Rag.Gamma mice injected i.v. with 2x105 Daudi/fLuc-GFP or with Jiyoye/fLuc-GFP cells. Compared with the non-treated controls, mice challenged with BL and treated with CD19KICAR-T cells showed delayed lymphoma dissemination with lower EBV DNA load. Notably, for the Jiyoye/fLuc-GFP model, almost exclusively CD4+ CD19KICAR-T were detectable at the endpoint analyses in the bone marrow, with increased frequencies of Tregs and TIM-3+CD4+ T cells. Administration of gp350KICAR-T cells into mice after Jiyoye/GFP fLuc challenge did not inhibit BL growth in vivo, but reduced the EBV DNA load in the bone marrow and promoted gp350 antigen escape. CD8+PD-1+LAG-3+ gp350KICAR-T cells were predominant in the bone marrow. Thus, the two types of KOTCRKICAR-T cells showed different therapeutic effects and in vivo dynamics. These findings reflect the complexities of the EBV’s immune escape mechanisms that may interfere with the CAR-T cell property and potency and should be taken in account for future clinical translation.